Nonlinear optical properties of Au@Ag coreshell nanospheres excited by femtosecond laser - Jun Wang (AIP Publishing LLC, 2021)
The nonlinear optical properties and ultrafast dynamics process of Au@Ag coreshell nanospheres (NSs) are reported in this paper. We researched the optical nonlinear absorption property of Au@Ag coreshell NSs excited by 800 nm laser at different energies by open-aperture Z-scan technology. The experimental results demonstrated that the Au@Ag coreshell NSs exhibited two-phone absorption (TPA) behavior, the degree of which was intensity-dependent. The TPA coefficients of Au@Ag coreshell NSs excited by different energies were obtained by fitting. By using pump-probe technology, we studied the ultrafast dynamics process of Au@Ag coreshell NSs. The results indicated that the relaxation process contained a fast and a slow process, which depended strongly on the laser intensity. By numerical fitting, we got the relaxation times of the sample excited at different laser powers.